Potential therapeutic option for EGFR-mutant small cell lung cancer transformation: a case report and literature review - Li, Xiaoxuan; Luan, Xinchi; Zhang, Mengqi; Wang, Rui; Guo, Jing; Lv, Jing; Qiu, Wensheng; Zhao, Shufen (Frontiers in Immunology, 2024)
Transformation from non-small cell lung cancer (NSCLC) to small cell lung cancer (SCLC) is rare and is associated with poor prognosis. However, the standard treatment protocols for patients with SCLC transformation remain unknown. Here, we report the case of a patient with advanced EGFR exon 19 deletion (19del) NSCLC who underwent SCLC transformation during targeted therapy. Biopsies and genetic testing were performed to adjust treatment regimens accordingly. The patient responded favorably to a combined treatment regimen comprising etoposide plus cisplatin chemotherapy and adebrelimab plus osimertinib. This case highlights the critical importance of acknowledging tumor heterogeneity in clinical decision-making and identifying potentially effective treatment options for patients with SCLC transformation. Additionally, we reviewed cases of the transformation of NSCLC to SCLC from 2017 to 2023.